Application of multi-criterion techniques on integral forest management in Durango, México - Pérez-Verdín, Gustavo; Hernández-Díaz, José Ciro; Márquez-Linares, Marco Antonio; Tecle, Aregai (Instituto de Ecología, A.C., 2016)
Traditionally, the forest capacity to produce multiple goods and services has been overlooked in favor of developing alternatives that maximize timber production or economic profit alone. This approach is suboptimal, it fails to address ecosystem interactions, and occasionally leads to degradation of some of its components. In this study, a technical framework to analyze and solve a multiobjective forest problem in an ejido of Durango, Mexico is presented. Forest inventory data and expert consultation were used to construct ten objective response functions expressed in terms of tree basal area, number of trees per hectare, and quadratic mean diameter. Compromise programming, a multiobjective decision-making technique was used to determine the most preferred solution of forest structures. Forest vegetation simulator and geographical information systems were used in order to evaluate the solutions for various clusters. The simulated optimal forest structures were typically above current stand conditions. These differences can be due to past management practices and other forest disturbances that reduced stocking and quality of residual trees. The use of this type of multiobjective decision making approach can help understand forest stand dynamics and long-term management of forest goods and services.